Occurrence of Ascaridia hermaphrodita (Nematode: Ascaridiidae) in Blue-Headed Parrot (Pionus menstruus) in Peru - Gómez Puerta, Luis A. (2008)
We report for first time the presence of nematode, Ascaridia hermaphrodita Froelich, 1789, parasiting small intestine  of a Blue-Headed Parrot (Pionus menstruus Linnaeus, 1776). The specimen was sent to Avian Pathology Laboratory of Veterinary School of San Marcos University, Lima, Peru. Eighteen nematodes (12 females and 6 males) were studied and identified as A. hermaphrodita. The dicovery of this specie in P. menstruus  is the first record in Perú.